Playing With a Concept: Teaching Job Characteristics Model With a Tinkertoy® Builder Set. (August 2013) - Smrt, Diana Lazarova; Nelson, Reed Elliot
Using a toy construction set, we introduce to students the job characteristics model in a fun and engaging way. The activity not only describes the theoretical variables of the model but also allows students to (a) experience the dynamic interaction among these variables and (b) gain a better, hands-on understanding of the model. The exercise progresses through three stages where participants are gradually exposed to different manipulations of the variables in the job characteristics model. The exercise can be conducted in one quick-paced 75-minute class session.